ANALYSIS OF ‘QIYAFAH’ PERSPECTIVE OF IMAM SYAFI`I IN PROVIDING THE LINEAGE AND ITS RELEVANCE WITH GENETICS - Abdul Hakim Hakm (State Islamic University of North Sumatra Indonesia, 2017)
In the tradition of Arab and Islamic Scientifics, research on genetics has been done since thousands of years ago. However, the information is not found in the books of genetic history. This indicates the existence of historical distortion of genetic history writers to include Arabs or Muslims within the span of history. Therefore, the follow-up and dissemination of information from various parties, especially the parties associated with genetic studies explain that this science has been found in Arab society and Muslims. Qiyafah is a method term used to recognize a person's trace in determining lineage based on traits and likeness. While qa`if, is a person who has special skills to see other people in connecting, determine the lineage based on the signs and similarities between the parties studied. According to asy-Shafi'i, qa'if services in determining one's lineage can be accepted as a legal provision. Therefore, if a lineage dispute arises where there is no other evidence or the parties have strong evidence, then the matter is solved by qa'if research. In support of his opinion, the school of ash-Shafi'i argued with the hadith of the Prophet Muhammad and the opinions of his companions. Therefore qiyafah practice is believed to have syariah justification.Genetika is one of the branches of biological science that discusses the nature of hereditary inheritance and variations that may arise in it. The practice of qiyafah and genetics are both aimed to examine the hereditary traits that are passed down from generation to generation. Judging from the similarity of function and purpose, then qiyafah has relevance to the science of genetics in establishing one's nasab. And the provision of modern science based on DNA test results with the same legal force with the provision of qiyafah perspective priest Shafi`i.Keywords: Qiyafah, Imam Syafi`i, Lineage, Genetics.